The Role of Financial Capability and Culture in Financial Satisfaction. Issue 4 (9th September 2020) - Çera, Gentjan; Khan, Khurram Ajaz; Belas, Jaroslav; Ribeiro, Humberto Nuno Rito
Abstract : This paper presents an integrated framework for understanding the determinants of financial satisfaction in the context of two European nations with different cultural environments. The direct, indirect and interactive effects were tested through the path analysis method. It was found that to be financially capable is imperative because it governs the impacts of financial attitude and financial knowledge on financial satisfaction. Moreover, findings show that culture matters in explaining differences between countries. Hence, individualistic societies, compared to collectivistic ones, reflect a stronger relationship between financial attitude and financial satisfaction. Additionally, countries showing a high propensity in avoiding uncertainty reflect a negative association between risk tolerance and financial satisfaction, while those lacking such preference manifest a positive relationship.